POLA PENDIDIKAN AGAMA DALAM KELUARGA JAMA’AH TABLIGH DI DESA BOLANG KECAMATAN DAYEUHLUHUR KABUPATEN CILACAP - Kholid Mawardi; Cucu Nurzakiyah (IAIN Purwokerto, 2019)
The results of the study found that the responsibility of religious education of children in the family of Tablighi Jama'ah differed in terms of several conditions, namely first, when parents were not going to khuruj where both parents were responsible for children's education; secondly, when the father goes khuruj, then the mother is responsible for everything including children's education; third, when both parents go khuruj, then the responsibility of the child is left to other family members such as grandparents or their first adult children; and fourth, when the child goes to khuruj, where parents are responsible for children's religious education both mother and father. The pattern of the religious education in the Tablighi Jama'ah family in the village of Bolang is formed from several similarities held in the implementation of religious education, one of which is the daily activity that is carried out by the Tablighi Jama'at family. Al-Qur'an becomes one of the material given to children in the ta'lim. Children are taught how to read the Qur'an and memorize short letters such as Surat al-Falaq, al-Ikhlas, and so on. In addition to al-Qur'an, in this ta'lim there is a special study in the Tablighi Jama'ah, which is reading the book of fadhilah ‘amal, and the last is mudzakarah six characteristics.